Exploring the impact of Artificial Intelligence on students' skills for sustainable development in education - Alkhawaja, Linda; Idris, Mohammed; Al-Sayyed, Sa'ida; Al Jaber, Abdul Malek (Frontiers in Education, 2025)
IntroductionIn today's rapidly evolving technological landscape, the integration of artificial intelligence (AI) into education is increasingly inevitable. AI has the potential to improve educational quality and, in turn, contribute to sustainable development. This study investigates the effects of selected AI tools; Grammarly, ChatGPT, QuillBot, Textero AI, and ChatPDF, on the quality of education and examines students' perceptions of their influence on self-directed learning, problem-solving, critical thinking, and digital literacy skills.MethodsA quantitative research design was adopted. Data were collected through a structured questionnaire and analyzed statistically using SPSS. Purposive sampling was employed, targeting 78 students enrolled in computer-aided translation courses over two semesters.ResultsThe findings indicated that students perceived multiple AI tools as beneficial in enhancing their learning skills, although the degree of impact varied across tools. Overall, the selected AI tools positively influenced skills associated with quality education, including self-directed learning, problem-solving, critical thinking, and digital literacy.DiscussionThe study demonstrates that AI tools can significantly contribute to the enhancement of educational quality. These findings underscore the importance of integrating AI technologies into teaching and learning processes to foster sustainable education. Future research should explore strategies for optimizing the use of AI tools in various educational contexts to maximize their potential benefits.